Determination of tetraniliprole residues in animal derived foods by multi-plug filtration cleanup combined with HPLC-MS/MS - YUAN Liejiang; WANG Xiu; LI Zheng; ZHU Li; DENG Hang (Shipin yu jixie)
ObjectiveThis study aimed to develop a rapid and efficient method for quantifying tetraniliprole residues in animal-derived foods by combining multi-plug filtration cleanup (m-PFC) with high-performance liquid chromatography-mass spectrometry (HPLC-MS).MethodsSamples were extracted with acetonitrile, followed by salting out using sodium chloride and anhydrous magnesium sulfate. The extracts were purified via m-PFC and analyzed using HPLC-MS with external standard calibration.ResultsThe method demonstrated a strong linear correlation between tetraniliprole concentration and response values over a range of 0.001 to 0.150 mg/L, with a coefficient of determination (R2) exceeding 0.999. The limit of quantification (LOQ) was 0.002 mg/kg. Average recovery rates ranged from 90.0% to 108.0%, with relative standard deviations between 1.10% and 4.89%, validated across a variety of matrices, including pork, beef, mutton, chicken, pork liver, beef liver, mutton liver, chicken liver, eggs and milk.ConclusionThe proposed method is rapid, straightforward, high sensitivity, and suitable for quantitative determination of tetraniliprole residues in animal-derived food.